The effects of work ethics on employee productivity in Jabatan Belia dan Sukan Paroi, Negeri Sembilan (JBSNS) / Nur Mawaddah Mauluddin - Mauluddin, Nur Mawaddah (Faculty of Business and Management, 2018)
This research is conducted to determine the effects of work ethics on employee productivity at Jabatan Belia dan Sukan, Paroi, Negeri Sembilan and need to find out the most influenced factors on this matter of interest towards employee productivity at this organization. The study was conducted by distributing 75 sets of questionnaires conveniently to each employee that work in Jabatan Belia dan Sukan Negeri Sembilan which included all Pejabat Belia dan Sukan Daerah (PBSD) in seven state which are Seremban, Rembau, Jelebu, Tampin, Jempol, Kuala Pilah and Port Dickson. A convenience sampling technique was used to select a sample of 75 respondents from a target population of 81 employees which only 74 questionnaires had been returned. Questionnaires were used to collect the primary data, meanwhile secondary data was collected through document, article and journal review. Based on data analysis, it found that from four independent variables develop in this study, only three variables have shown a significant relationship towards employee productivity which are the teamwork, work attitude and discipline which they have effects on employee productivity while commitment not. Regarding the findings, it can be concluded that the respondents highly agreed that teamwork, work attitude and discipline have effects on their productivity at workplace while commitment not. It shows that all of the independent variables; work attitude, commitment, teamwork and discipline have positive relationship towards employee productivity. The most influential factor of all the variables is teamwork which describes that they have good relationship among employees in managing tasks together.